Nitrogen-Doped Carbon Dots Encapsulated a Polyoxomolybdate-Based Coordination Polymer as a Sensitive Platform for Trace Tetracycline Determination in Water - Yanqiu Zhang; Minrui Sun; Yang Lu; Mingguo Peng; Erdeng Du; Xia Xu (Nanomaterials, 2023)
The requirement of simple, efficient and accurate detection of tetracycline (TC) in water environments poses new challenges for sensing platform development. Here, we report a simple method for TC sensing via fluorescence detection based on metal–organic coordination polymers (MOCPs, (4-Hap)4(Mo8O26)) coated with nitrogen-doped carbon dots (NCDs). These NCDs@(4-Hap)4(Mo8O26) composites showed excellent luminescence features of NCDs with stable bright-blue emission under UV light. The results of the sensing experiment showed that the fluorescence of NCDs@(4-Hap)4(Mo8O26) can be quenched by TC (166 µM) with 94.1% quenching efficiency via the inner filter effect (IFE) in a short time (10 s), with a detection limit (LOD) of 33.9 nM in a linear range of 8–107 µM. More significantly, NCDs@(4-Hap)4(Mo8O26) showed a high selectivity for TC sensing in the presence of anions and metal cations commonly found in water environments and can be reused in at least six cycles after washing with alcohol. The potential practicality of NCDs@(4-Hap)4(Mo8O26) was verified by sensing TC in real water samples with the standard addition method, and satisfactory recoveries from 91.95% to 104.72% were obtained.